Accountability of Village Funds in the Daily Practices of Stakeholders: An Ethnomethodological Analysis - PRILIANDANI, Ni Made Intan; KRISTIANTARI, I Dewa Ayu; MIATI, Ni Luh Putu Mita (Journal of Governance, Taxation and Auditing, 2025)
The management of Village Funds requires an accountability system that extends beyond administrative compliance and is instead constructed through the everyday practices of village stakeholders. This study seeks to examine how Village Fund accountability is produced and sustained through the social methods employed by village actors in their routine interactions. A qualitative ethnomethodological approach was adopted. Data were collected through in-depth interviews, participant observation, and document analysis involving the village head, village officials, the Village Consultative Body (BPD), community leaders, and other resident groups. The findings indicate that accountability is generated through five forms of social practice. First, accountability emerges through reflexive practices, in which the actions of village officials simultaneously serve as explanations and justifications. Second, the meaning of accountability is indexical, shaped by cultural context, religious values, customary structures, and locally embedded interactional patterns. Third, accountability is enacted through accountable actions, namely actions that are intentionally made understandable to the public. Fourth, both officials and residents rely on practical reasoning in interpreting and evaluating accountability, such that assessments of integrity extend beyond documentary evidence. Fifth, various local members' methods, including communal deliberation (musyawarah), verbal communication, informal social monitoring, and the moral principle of amanah (trustworthiness), function as living, socially embedded governance mechanisms that effectively reinforce accountability. Methodologically, the study demonstrates the utility of ethnomethodology for examining village governance and highlights the importance of locally grounded practices in strengthening accountability systems.